Langgam Buya Syafii Merawat Rindu dan Nurani - Muzir, Ridwan (MAARIF Institute, 2023)
Buya Syafii Maarif conveys his critical thoughts through sharp and readable writing. In some of his writings, Buya Syafii uses elements of Minang language which is his mother tongue. This method makes the writing have its own amazing characteristics. This article will discuss the figure of Buya Syafii who is behind the Minang style of speaking Indonesian. The focus will be on how Buya chooses Minang style words and expressions and the context of the ideas and thoughts that underlie them, as well as why he uses Minang linguistic elements in some of his writings. By positioning Buya as a subject who is conveying/ expressing something (the subject of enunciation), this paper finds that his writings in the Minang style are an expression of a dialectical way of thinking and an expression of longing for the Ideal.